Combined turbo equalization and turbo decoding - Raphaeli, D.; Zarai, Y. (IEEE communications letters, 1998)
In this letter, the subject of turbo coding in the presence of an intersymbol interference channel is investigated. An iterative decoder structure is presented, which combines channel equalization and turbo decoding. At each iteration extrinsic information from the channel detector is fed into the turbo decoders, and then their extrinsic information is fed back to the channel detector. Simulation results are presented for a rate 1/2 turbo code with binary phase-shift keying (BPSK) modulation, transmitted over an intersymbol interference (ISI) channel having severe frequency distortion. The performance is about 0.8 dB from the ISI channel capacity at a bit-error rate of 10/sup -5/.